Atherosclerotic Lesions in the Superficial Femoral Artery (SFA) Characterized with Velocity Ratios using Vector Velocity Ultrasound - Hansen, Peter Møller; Hansen, Kristoffer Lindskov; Pedersen, Mads Møller; Lange, Theis; Lönn, Lars; Jensen, Jørgen Arendt; Nielsen, Michael Bachmann (Ultrasound International Open, 2018)
Purpose Atherosclerotic arteries are challenging to evaluate quantitatively using spectral Doppler ultrasound because of the turbulent flow conditions that occur in relation to the atherosclerotic stenoses. Vector velocity ultrasound is angle independent and provides flow information, which could potentially improve the diagnosis of arterial stenoses. The purpose of the study is to distinguish significant stenoses in the superficial femoral artery (> 50% diameter reduction) from non-significant stenoses based on velocity ratios derived from the commercially available vector velocity ultrasound technique Vector Flow Imaging (VFI).Materials and Methods Velocity ratios (intrastenotic blood flow velocity divided by pre- or poststenotic velocity) from a total of 16 atherosclerotic stenoses and plaques in the superficial femoral artery of 11 patients were obtained using VFI. The stenosis degree, expressed as percentage diameter reduction of the artery, was determined from digital subtraction angiography and compared to the velocity ratios.Results A velocity ratio of 2.5 was found to distinguish clinically relevant stenoses with>50% diameter reduction from clinically non-relevant stenoses with<50% diameter reduction and the difference was statistically significant.Conclusion The study indicates that VFI is a potential future tool for the evaluation of arterial stenoses.
Keywords: angiography; velocity ratio; atherosclerosis; peripheral arterial disease; vector velocity ultrasound